2020
DOI: 10.1111/ppc.12672
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interpersonal relational role analysis on nursing students' anxiety levels and interpersonal problem‐solving orientation

Abstract: Purpose: This study has been performed to investigate the effects of the interpersonal relational role analysis (IRRA) on the nursing students' anxiety levels and their interpersonal problem-solving orientation.Design and Methods: This study was conducted with randomized controlled, pretest-post-test control group design and follow-up test patterns (n = 8).Finding: Following the practice of IRRA sessions, the findings showed that IRRA has a positive effect on the anxiety levels and interpersonal problem-solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…According to the results obtained, the present study is along the results of the study Basharat et al [36] which showed that there is a positive relationship between other-oriented and community-oriented perfectionism with symptoms of depression and anxiety, and this finding is also consistent with the results of Stoeber et al [37]; Smith et al [38]; Cha et al [39]; Chang et al [40]; Sherry et al [41]; Lasota and Kearney [42]; Lessin and Pardo [43]. Moreover, previous study mentioned that interpersonal relational role systems are an important support in reducing the relational stress experienced by nurses [44].…”
Section: Discussionsupporting
confidence: 86%
“…According to the results obtained, the present study is along the results of the study Basharat et al [36] which showed that there is a positive relationship between other-oriented and community-oriented perfectionism with symptoms of depression and anxiety, and this finding is also consistent with the results of Stoeber et al [37]; Smith et al [38]; Cha et al [39]; Chang et al [40]; Sherry et al [41]; Lasota and Kearney [42]; Lessin and Pardo [43]. Moreover, previous study mentioned that interpersonal relational role systems are an important support in reducing the relational stress experienced by nurses [44].…”
Section: Discussionsupporting
confidence: 86%
“…Such exposure, which may accompany them throughout their professional life, enables nurses to easily adapt to traumatic situations psychologically and even create a potential for additional personal development Pan Cui et al, 2020;Vazquez et al, 2020). It is vital for nursing students, being future nurses, to have such development potential regarding their professional and social lives (Li et al, 2015;Kaplan and Ançel, 2020). COVID-19, a traumatic experience, has been a devastating factor for nursing students as well as individuals from every segment of society.…”
Section: Introductionmentioning
confidence: 99%